Implementasi Prinsip Konvensi Internasional dalam Mengurai Pelanggaran HAM di Indonesia - Muhammad Mutawalli (Jurnal Arajang, 2023)
The purpose of this research is to find out the form of implementation of the principles and obstacles to the enforcement of human rights violations in Indonesia and their relationship to the content of international conventions. The approach used in this study is a normative legal approach. This research is related to the legal study of library materials. The results of research conducted regarding the implementation of human rights principles are in line with international legal agreements in the Indonesian legal system in general, but the constraints or obstacles are still not very effective in overcoming discrimination violations based on the principle of equality, with international agreements on human rights. It is different in Indonesia, its implementation has been regulated in the initiative of national laws and regulations related to human rights contained in the 1945 Constitution. This means that it has been in effect since the time of Indonesia's independence.